French Colonial Fascism - Kalman, S. author. aut Link
XI, 286 p.
Keywords: This study investigates the various extreme-rightist leagues in Algeria, with particular attention to certain key themes, among them the rabid xenophobia directed at the Jewish population and local Muslims. It demonstrates that fascism helped to construct a racial hierarchy to preserve European hegemony and a pool of cheap labor.